Corporate governance codes and their contents: An analysis of Eastern European codes - Niels Hermes; Theo J. B. M. Postma; Orestis Zivkov (Journal for East European Management Studies, 2007)
Existing literature suggests that the contents of corporate governance codes are similar due to external forces, such as increased integration of countries in the global economy, the increased role of foreign institutional investors and recommendations on corporate governance practices of international organisations. This paper analyzes and compares the code contents of seven Eastern European countries with respect to generally accepted best practice recommendations on disclosure rules, strengthening shareholder rights and modernising boards. We show that for some countries the contents of the country codes are actually rather different as compared to these best practices, suggesting that domestic forces related to country-specific characteristics of corporate governance systems may have helped shaping the contents of corporate governance codes. – – Die bisherige Fachliteratur argumentiert, dass die Inhalte der Corporate Governance Kodizes relativ ähnlich sind aufgrund von externen Faktoren wie der wachsenden Integration der Länder in die globale Wirtschaft, der verstärkten Rolle von ausländischen institutionellen Investoren und den Empfehlungen für Corporate Governance - Praktiken in internationalen Organisationen. Dieser Aufsatz analysiert und vergleicht die Inhalte der Kodizes von sieben osteuropäischen Ländern im Hinblick auf allgemein akzeptierte best practice - Empfehlungen bezüglich Offenlegung, Stärkung der Aktionärsrechte und der Modernisierung der Führungsgremien. Wir zeigen auf, dass in einigen Ländern die Kodizes stark von den best practice - Empfehlungen abweichen, was darauf hinweist, dass lokale Kräfte mit Bezug auf die Eigenheiten des nationalen Corporate Governance Systems die Entwicklung der Kodizes wesentlich geprägt haben.
Keywords: 650; corporate governance; corporate governance codes; Eastern Europe